Honokiol Inhibits the Inflammatory Response and Lipid Metabolism Disorder by Inhibiting p38α in Alcoholic Liver Disease - Yang, Chenchen; Zhao, Yinglian; Luo, Zhipan; Hu, Ying; Wang, Shuxian; Hu, Shuang; Yao, Yan; Pan, Linxin; Shen, Chuanpu; Xu, Tao (Planta Medica, 2023)
Alcoholic liver disease is one of the leading causes of liver-related morbidity and mortality worldwide, but effective treatments are still lacking. Honokiol, a lignin-type natural compound isolated from the leaves and bark of Magnolia plants, has been widely studied for its beneficial effects on several chronic diseases. Accumulating studies have revealed that honokiol displays a potential therapeutic effect on alcoholic liver disease. In this study, the protective activity of honokiol on alcoholic liver disease was confirmed due to its significant inhibitory activity on the expression levels of inflammatory cytokines (such as tumor necrosis factor-alpha, interleukin-6, and interleukin-1β) in EtOH-fed mice and in EtOH-induced AML-12 cells. Meanwhile, the expression of the lipid metabolic parameter sterol regulatory element-binding protein-1c was also reduced. However, peroxisome proliferator-activated receptor α was increased in animal and cell experiments, which indicates that the activity of honokiol was related to its regulated activity on lipid metabolism. The result showed that honokiol significantly inhibited the expression level of p38α in vivo and in vitro. Blocking p38α inhibited the expression levels of tumor necrosis factor-alpha, interleukin-6, interleukin-1β, and sterol regulatory element-binding protein-1c but promoted the expression level of peroxisome proliferator-activated receptor α compared with the honokiol-treated group. Moreover, the forced expression level of p38α further produced the opposite effect on inflammatory cytokines and lipid metabolism indicators. Furthermore, p38α has been related to the activation of the nuclear factor kappa B signaling pathway. In our study, honokiol significantly inhibited the activation of the nuclear factor kappa B signaling pathway mediated by p38α. In conclusion, the results suggest that honokiol might be an effective regulator of p38α by downregulating the nuclear factor kappa B signaling pathway, thereby reducing the inflammatory response and lipid metabolism disorder in alcoholic liver disease.
Keywords: honokiol; alcoholic liver disease; p38α; inflammation; lipid metabolism; NF-κB; Magnolia officinalis; Magnoliaceae